2021
DOI: 10.3389/fphys.2021.734509
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Joint Angles in Elbow Flexor Unilateral Resistance Exercise Training Determine Its Effects on Muscle Strength and Thickness of Trained and Non-trained Arms

Abstract: The present study compared two unilateral arm curl resistance exercise protocols with a different starting and finishing elbow joint angle in the same ROM for changes in elbow flexors strength and muscle thickness of the trained and non-trained arms. Thirty-two non-resistance trained young adults were randomly assigned to one of the three groups: extended joint training (0°–50°; EXT, n = 12); flexed joint training (80°–130°; FLE, n = 12); and non-training control (n = 8). The exercise training was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…Even if the current results are in line with previous research (Sato et al 2021), other authors have found no differences in regional hypertrophy of the arm muscles after performing preacher curls (Drummond et al 2016). However, in this study the special equipment used placed the major di culty when the biceps brachii was in a shortened position, and all the subjects performed preacher curls (not any other exercise, with any special kind of resistance) which shows the importance of mechanical stimuli and resistance pro les for regional hypertrophy (Franchi et al 2018b).…”
Section: Fages Et Al 2022)supporting
confidence: 91%
See 1 more Smart Citation
“…Even if the current results are in line with previous research (Sato et al 2021), other authors have found no differences in regional hypertrophy of the arm muscles after performing preacher curls (Drummond et al 2016). However, in this study the special equipment used placed the major di culty when the biceps brachii was in a shortened position, and all the subjects performed preacher curls (not any other exercise, with any special kind of resistance) which shows the importance of mechanical stimuli and resistance pro les for regional hypertrophy (Franchi et al 2018b).…”
Section: Fages Et Al 2022)supporting
confidence: 91%
“…This data shows once again the in uence of contraction type in regional hypertrophy, and outlines the importance of standardizing the time spent performing concentric or eccentric actions during a repetition in regional hypertrophy studies to avoid confusion factors. However, it should be noted that the distal part of the arm is the biggest one (Matta et al 2011;Sato et al 2021), and for that reason it is also the one we should expect to grow the most (at least in terms of absolute growth). In fact, growth in the most distal part of the arm can be found in 4 studies (including the present one), while the rest of the regions do not always grow (Matta et al 2011;Yasuda et al 2015;Sato et al 2021).…”
Section: Fages Et Al 2022)mentioning
confidence: 99%
“…The authors postulated that this finding was likely because of the implementation of the incline dumbbell curl; given the more elongated position of the biceps, this exercise potentially favors stretch-mediated hypertrophy (14,42). This hypothesis is supported by emerging evidence demonstrating the superiority of training certain muscles in more stretched positions (28,38,41). Hence, these 2 studies (14,20) taken together with previous findings (5,10) suggest that exercise variation should be carefully planned and implemented to optimize benefits from exercise variation.…”
Section: Main Outcomesmentioning
confidence: 98%
“…8 Several studies published subsequent to that paper have shown greater hypertrophy at longer versus shorter muscle lengths in dynamic training of the hamstrings 9 and biceps brachii. 10 Most recently, Pedrosa et al 7 found that pROM knee extension training at a long muscle length was at least as effective, and in some cases superior, in eliciting increases in quadriceps CSA compared to fROM training.…”
Section: Partial Range Of Motion and Muscle Hypertrophy: Not All Roms...mentioning
confidence: 99%